A Study of the Use of the HAT Afrikaanse Skoolwoordeboek by Primary School Children - Michele F. van der Merwe (Woordeboek van die Afrikaanse Taal-WAT, 2012)
A research project on the use of the HAT Afrikaanse Skoolwoordeboek by primary school learners is described. (In South Africa the term learner is used to describe a pupil at school). Studies on the way in which learners use dictionaries provide valuable information for both lexicographers and language teachers. The assessment of users' skills regarding the use of the HAT Afrikaanse Skoolwoordeboek was made in the learners' home language. In order to design a test to assess dictionary skills regarding the language learning outcomes of Grade 4 learners, the language learning assessment outcomes in the Grade 4 Afrikaans home language curriculum had to be unwrapped. The process was undertaken in cooperation with Grade 4 teachers to ensure that a realistic assessment of dictionary skills was made and an assessment of dictionary skills of 200 learners ensued. The assessments were marked, marks were calculated and results were analysed. Teachers were trained in teaching dictionary learning strategies and language skills. Learners then received training from their teachers to extract semantic information from a dictionary, as this proved to be the most difficult skill to master, according to the results of the assessment.